The tale of Despereaux : being the story of a mouse, a princess, some soup, and a spool of thread - DiCamillo, Kate.; Ering, Timothy B. (2013)
The adventures of Desperaux Tilling, a small mouse of unusual talents, the princess that he loves, the servant girl who longs to be a princess, and a devious rat determined to bring them all to ruin. Includes Kate DiCamillo's Newbery Medal acceptance speech, Q&A with Kate DiCamillo, and Q&A with Timothy Basil Ering.
M
b
b
Keywords: Fairy tales; Mice -- Fiction